2006
DOI: 10.1002/jssc.200500330
|View full text |Cite
|
Sign up to set email alerts
|

Application of cyclodextrins as modifiers in electrophoretic separation of metalloporphyrins

Abstract: Several metallocomplexes of tetrakis-carboxyphenylporphyrin (TCPP) were separated on fused-silica capillary using CZE with UV-VIS detection. Metalloporphyrins of Co(II), Cu(II), Mn(II), Ni(II), and Zn(II) were formed directly in TCPP solution with addition of Cd(II) to increase the formation reaction rate. The composition of BGE, its concentration, and pH were optimized to ensure the stability of complexes and proper resolution. In particular, the problem of signals' shape was investigated and discussed. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Adsorption of organic compounds by CNPs in aqueous phases is a critical process for environmental application of CNPs in water treatment ,, and solid-phase extraction as superior sorbents and in synthesis of functionalized CNPs with desired and tunable physical and chemical properties . This process is also important for determining the environmental and health impacts of both CNPs and organic chemicals. , First, adsorption of natural organic matter and surfactants on CNPs would enhance their suspension and stability in water and, consequently, alter the environmental fate and transport of CNPs. Second, adsorbed organic chemicals such as hydrophobic organic compounds (HOCs) may add additional toxicity to that of CNPs when these CNPs are taken up by and accumulated in organisms. ,, Third, CNPs would act similarly to other “hard” carbon materials such as charcoal and soot , in the environment and alter the fate, transfer, and bioavailability of environmental organic pollutants by adsorption. , For example, the bioavailability and mobility of organic pollutants into organisms could be reduced and, consequently, their persistence in the environment would be enhanced if they are adsorbed by a CNP which cannot be taken up by or accumulated in the organisms .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption of organic compounds by CNPs in aqueous phases is a critical process for environmental application of CNPs in water treatment ,, and solid-phase extraction as superior sorbents and in synthesis of functionalized CNPs with desired and tunable physical and chemical properties . This process is also important for determining the environmental and health impacts of both CNPs and organic chemicals. , First, adsorption of natural organic matter and surfactants on CNPs would enhance their suspension and stability in water and, consequently, alter the environmental fate and transport of CNPs. Second, adsorbed organic chemicals such as hydrophobic organic compounds (HOCs) may add additional toxicity to that of CNPs when these CNPs are taken up by and accumulated in organisms. ,, Third, CNPs would act similarly to other “hard” carbon materials such as charcoal and soot , in the environment and alter the fate, transfer, and bioavailability of environmental organic pollutants by adsorption. , For example, the bioavailability and mobility of organic pollutants into organisms could be reduced and, consequently, their persistence in the environment would be enhanced if they are adsorbed by a CNP which cannot be taken up by or accumulated in the organisms .…”
Section: Introductionmentioning
confidence: 99%
“…Polanyi theory-based models have been successfully used to fit the adsorption isotherms. ,, Adsorption mechanisms of organic compounds on CNTs from aqueous solution have been partly summarized by Pan and Xing . Carbon nanotubes as solid-phase extraction material and sorbents have also been partly reviewed in previous works. ,, However, Polanyi theory and its application in describing organic chemical adsorption by CNPs are not discussed in these review papers. Empirical relationships, relating the adsorption capacity and affinity of CNPs with the CNP/organic chemical structures and physicochemical properties, are also not reviewed, but these empirical relationships can be helpful to explore the adsorption mechanisms and to estimate the adsorption capacity and affinity, and then one can evaluate the potential application of CNPs as sorbents and influence of adsorption on the environmental risks of both toxic organic chemicals and CNPs.…”
Section: Introductionmentioning
confidence: 99%
“…There is rapidly developing interest to the function of macrocyclic host molecules as metal complex carrier, which is important for drug delivery [4][5][6]. The other areas, where inclusion compounds of metal complexes into cavitands can find or have already found applications, are design of molecular machines [7,8], enantioselective and size-dependent molecular separation [9,10], and catalysis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…23 Owing to their highly porous and hollow structure, large specific surface area, light mass density, and the strong interaction between CNTs and pollutant molecules, the application of CNTs for the removal of hazardous pollutants from a large volume of aqueous solutions has been studied extensively in recent years. [24][25][26][27][28] Long and Yang reported a significantly higher dioxin removal efficiency with CNTs than that with AC. 29 Li et al found that CNTs have high lead adsorption capacity and can be used as an adsorbent for lead and fluoride removal from water.…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of CNT structures, the relationship between CNTs and other carbonaceous adsorptive materials is almost the same as that between single crystals and polycrystalline materials . Owing to their highly porous and hollow structure, large specific surface area, light mass density, and the strong interaction between CNTs and pollutant molecules, the application of CNTs for the removal of hazardous pollutants from a large volume of aqueous solutions has been studied extensively in recent years . Long and Yang reported a significantly higher dioxin removal efficiency with CNTs than that with AC .…”
Section: Introductionmentioning
confidence: 99%